Pengaruh Corporate Governance Terhadap Kinerja Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2014 - 2017 (Studi pada Perusahaan yang Memperoleh CGPI Tahun 2014 – 2017) - Eva Setiarini Damanik; Yulia Istia Ningsih (Universitas Batanghari Jambi, 2019)
The objectives of this study is to find out the influence of good corporate governance (GCG) towards the corporate performance. Independent variable in this research is good corporate governance. This variable is measured with an instrument developed by IICG in the form of corporate governance perception index (CGPI). CGPI contains the score of the survey’s result related to the application of corporate governance by the Companies throughout Indonesia. Meanwhile the dependent Variable of this research is the Performance of the Company on their finances measured with “return on equity and Tobin’s Q. The Sample of this study is company which is registered in Indonesian Stock Exchange and joined CGPI Programs in 2014, 2015, 2016 and 2017 taken by using purposive sampling method. This study used simple linear regression analysis method. The result of this study : (1) Corporate governance has a positive impact on ROE (2) Corporate governance has not an impact on Tobin’s Q